EMERGÊNCIA E CRESCIMENTO INICIAL DA SOJA SUBMETIDA AO ESTRESSE POR ENCHARCAMENTO - BORTOLAZZO, Guilherme; OLIVEIRA, Camilla Paulino de; DOURADINHO, Gabriel Zanuto; ANDRADE, Agner de Freitas; ZOZ, Tiago (ANAIS DO ENIC, 2018)
-